Local Community Role in Sustainable Tourism in Saribu Gonjong Village West Sumatra - Berutu, Feronika; Husna, Rifdatul; Natasha, Graciella (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2025)
Sustainable tourism can create a positive relationship between tourism and the local environment through three main dimensions: physical environment, socio-cultural sustainability, and economic sustainability. The local community plays an important role in supporting sustainable tourism. Saribu Gonjong Tourism Village (SARUGO), located in West Sumatra, is known for the Minangkabau community life, traditional Rumah Gadang houses, and distinctive cultural dances. This cultural potential needs to be preserved sustainably. However, the community’s role in supporting sustainable tourism is still not optimal, so a more focused Sustainable Tourism concept is needed. The research used a descriptive qualitative method with primary and secondary data collected through in-depth interviews, participatory observation, and documentation. Saribu Gonjong Village was established in 2019 and is managed collaboratively by the local community, Pokdarwis (Tourism Awareness Group), and village leaders who actively preserve culture and develop tourism potential. The village also opens economic opportunities through homestays, crafts, and agro-tourism, although promotion and facilities need improvement. Capacity building, especially for the younger generation, is conducted through art and cultural training. With enhanced training and wider community involvement, Saribu Gonjong Tourism Village has the potential to become a leading, sustainable destination that improves the community’s welfare.